Selecting goldfish broods use the weighted product and simple additive weighting methods - Ramadiani Ramadiani; Surya Adithama; Muhammad Labib Jundillah (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
Majalaya carp is a freshwater fish that has important economic value and is widespread in Indonesia. Goldfish is the most cultivated fish because it has many advantages both physiologically and genetically. Several factors of assessment in the selection of superior brood stock that can be considered in the cultivation of goldfish cultivators are; ideal body weight, fish movement, physical deformities, scales, and the base of the tail. All of these factors can help in the decision-making process for superior goldfish. This study uses two methods, namely the simple additive weighting (SAW) method and the weighted product (WP) method. Based on the results of research that has been carried out on 20 superior broodfish of Majalaya goldfish, the level of accuracy is obtained by comparing with existing data. The WP method gets an accuracy value of 90% while the SAW method gets an accuracy value of 80%.